A „maradék” Biharország fővárosa: Berettyóújfalu. Berettyóújfalu vonzáskörzete - Gyöngyösi, László (Tér és Társadalom, 1996)
The study attempts to introduce those functions of the town which have a significant attraction zone, without a more detailed historical background, mainly concentrating on the present situation. My work was greatly helped and historical comparisons of smaller scale were made possible by the fact that Tibor Mendöl in the 1950s, Pál Beluszky in 1962 and Bálint Csatári in 1977 had already examined the problems in the attraction zone of Berettyóújfalu. From those functions which have a significant attraction zone, the following are dealt with here in more details: Public admínístration and public institutions, retail trade, secondary education, health care and tourism. With the help of the available data, as a summary I try to designate the complex attraction zone of the town.